Mixed higher-order anisotropic flow and nonlinear response coefficients of charged particles in PbPb collisions at √sNN=2.76 and 5.02TeV; European Physical Journal C; Vol. 80, iss. 6 - Sirunyan A. M.; Tumasyan A. R.; Adam W. Wolfgang; Ambrogi F. Federico; Tyurin N. E. Nikolay Evgenjevich; Babaev A. A. Anton Anatoljevich (2020, 2020)
Title screen